Comparative habitat selection by muskoxen introduced to northeastern Alaska and the Taimyr Peninsula, Russia - Klein, David R.; Yakushkin, Gregory D.; Pospelova, Elina B. (Rangifer, 1993)
Muskoxen (Ovibos moschatus) introduced to formerly occupied areas in northeastern Alaska (70°N) in 1969 and 1970, and the Taimyr Peninsula (75°N) in 1974 and 1975 increased in number (exceeding 20%/year in the early years following their establishment), and have expaned into available habitats. Vegetation of the two areas share many similarities, although richness of vascular plant species is greater in Alaska (350) than in the Taimyr (230). Seasonal partitioning of range use is similar in both areas with low-lying tussock tundra being used primarily from summer through early to mid-winter. By late winter, when snow accumulation in low areas and on lower slopes of hills limits access to forage, muskoxen concentrate activity on drier ridge tops and river and coastal bluffs with little snow accumulation. Riparian habitats appear to receive greater year round use in Alaska than in the Taimyr.